Erythropoietin as a Neuroprotective Drug for Newborn Infants: Ten Years after the First Use - Serafina Perrone; Chiara Lembo; Federica Gironi; Chiara Petrolini; Tiziana Catalucci; Giulia Corbo; Giuseppe Buonocore; Eloisa Gitto; Susanna Maria Roberta Esposito (MDPI AG, 2022)
Protective strategies against perinatal brain injury represent a major challenge for modern neonatology. Erythropoietin (Epo) enhances endogenous mechanisms of repair and angiogenesis. In order to analyse the newest evidence on the role of Epo in prematurity, hypoxic ischemic encephalopathy (HIE) and perinatal stroke, a critical review using 2020 PRISMA statement guidelines was conducted. This review uncovered 26 clinical trials examining the use of Epo for prematurity and brain injury-related outcomes. The effects of Epo on prematurity were analysed in 16 clinical trials. Erythropoietin was provided until 32-35 weeks of corrected postnatal age with a dosage between 500-3000 UI/kg/dose. Eight trials reported the Epo effects on HIE term newborn infants: Erythropoietin was administered in the first weeks of life, at different multiple doses between 250-2500 UI/kg/dose, as either an adjuvant therapy with hypothermia or a substitute for hypothermia. Two trials investigated Epo effects in perinatal stroke. Erythropoietin was administered at a dose of 1000 IU/kg for three days. No beneficial effect in improving morbidity was observed after Epo administration in perinatal stroke. A positive effect on neurodevelopmental outcome seems to occur when Epo is used as an adjuvant therapy with hypothermia in the HIE newborns. Administration of Epo in preterm infants still presents inconsistencies with regard to neurodevelopmental outcome. Clinical trials show significant differences mainly in target population and intervention scheme. The identification of specific markers and their temporal expression at different time of recovery after hypoxia-ischemia in neonates might be implemented to optimize the therapeutic scheme after hypoxic-ischemic injury in the developing brain. Additional studies on tailored regimes, accounting for the risk stratification of brain damage in newborns, are required.